2015
DOI: 10.1093/annonc/mdv270
|View full text |Cite
|
Sign up to set email alerts
|

First-line erlotinib versus gemcitabine/cisplatin in patients with advanced EGFR mutation-positive non-small-cell lung cancer: analyses from the phase III, randomized, open-label, ENSURE study

Abstract: These analyses demonstrate that first-line erlotinib provides a statistically significant improvement in PFS versus GP in Asian patients with EGFR mutation-positive NSCLC (NCT01342965).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
493
2
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 668 publications
(522 citation statements)
references
References 18 publications
19
493
2
8
Order By: Relevance
“…Based on results from seven prospective phase III randomized trials comparingfirst-line epidermal growthfactor receptor(EGFR) tyrosine kinase inhibitors (TKIs) to platinum-doublet chemotherapy as first-line treatment of non-small cell lung cancer (NSCLC) patients harboring activating EGFR mutations (EGFRm), it is now well-established that EGFR TKI offers superior improvement in progression-free survival (PFS) [1][2][3][4][5][6][7]. Exploratory univariate analyses of three of the seven clinical trials (WJTOG3405, EURTAC, and LUX-Lung-3 [LL3]) suggested that EGFRm NSCLC patients who had a previous smoking history (former or current smoker) did not seem to derive a statistical PFS improvement when EGFR TKI was compared with platinum-doublet chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on results from seven prospective phase III randomized trials comparingfirst-line epidermal growthfactor receptor(EGFR) tyrosine kinase inhibitors (TKIs) to platinum-doublet chemotherapy as first-line treatment of non-small cell lung cancer (NSCLC) patients harboring activating EGFR mutations (EGFRm), it is now well-established that EGFR TKI offers superior improvement in progression-free survival (PFS) [1][2][3][4][5][6][7]. Exploratory univariate analyses of three of the seven clinical trials (WJTOG3405, EURTAC, and LUX-Lung-3 [LL3]) suggested that EGFRm NSCLC patients who had a previous smoking history (former or current smoker) did not seem to derive a statistical PFS improvement when EGFR TKI was compared with platinum-doublet chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…The HR for PFS among former/current smokers in OPTIMAL was 0.21 (95% CI: 0.09-0.49) [3]. The HR for PFS among current or ex smokers in LL6 was 0.46 (95% CI: 0.22-1.00) [6].Two remaining trials (NEJ002 and ENSURE) have not reported univariate analysis by smoking status [2,7]. Given that up to one-third of EGFRm patients had a previous smoking history [8], we performed a meta-analysis to analyze the role of smoking status and other potential predictive factors that may influence clinical outcome in EGFRm patients receiving firstline EGFR TKIs.…”
Section: Introductionmentioning
confidence: 99%
“…[17] The use of ctDNA has been successfully shown to predict the clinical benefit of erlotinib in patients with EGFR mutations detected on ctDNA leading to its FDA approval using the companion COBAS EGFR mutation test v2. [18,19] Difficult to diagnose cancers Inaccessible tumors such as deep pelvic, pancreatic, and bone tumors can be diagnosed with CTCs or ctDNA. There are case reports where synchronous versus metastatic malignancies have been identified by detecting different set of specific mutation.…”
Section: Taking Therapeutic Decisions Based On Liquid Biopsymentioning
confidence: 99%
“…Patients with NSCLC with IIIB and IV have particularly poor prognoses. In the last decade, the me-dian overall survival of the patients with metastatic NSCLC treated systemically within clinical studies, have grown from a few months to more than 20 months as reported in some studies results [4][5][6][7]. This improvement was obtained thanks not only to the modification of the previous treatment regimens [8][9][10][11], but first of all thanks to the application of new drugs, such as epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKI) and ALK inhibitors [12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%